If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + c = 5y Reorder the terms: c + 3x = 5y Solving c + 3x = 5y Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3x' to each side of the equation. c + 3x + -3x = -3x + 5y Combine like terms: 3x + -3x = 0 c + 0 = -3x + 5y c = -3x + 5y Simplifying c = -3x + 5y
| .07x+.38=-.16-.05x | | 1-5(2x-4)=12 | | 3x+5+12x+7x=-14x-12+1 | | 0=x^2-5x+6 | | 12y-5=24y+4-13 | | -12w-4+3w-7=4 | | 3(5y-3)=6y | | 3x-4x-4=0 | | 4y+14=3 | | 6y-3(y-3)+6= | | 5p-22=-30+4p | | 3x-29=-23+9x | | 6.75+b=7.5 | | 66.8*2x=30 | | B=yx+m | | -x^2-3x-8=0 | | w/10=6 | | -1/6-7-7 | | 125x^3-216r^3= | | d-9=-16 | | 5/9(77-32) | | -x/-6=10 | | -(1/5)x-4 | | 8x^3-24x^2-1664x= | | 1/3*(2x-5)=3 | | 7s^2+19s+10= | | y=3x^2-30x+71 | | 2x+2x+5=17 | | 315=5x^3 | | 8p^2-21p-36=0 | | C=200+.75Y | | (4v-3p)(4v+2p)= |